What You Should Know Before Planning Your Citrus Weed Management Program - Richard S. Buker, III (EDIS)
This publication provides an overview of the principles upon which a successful weed management program is built. In this publication the author distinguishes the important differences between weed management and weed control. A typical decision process of planning a weed management program as well as some important factors that impact tree growth and yield are also discussed. This document is HS999, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March, 2005.